PENENTUAN FAKTOR-FAKTOR PRIORITAS YANG MEMPENGARUHI MASYARAKAT DALAM PENGGUNAAN BUS TRANS METRO DELI MEDAN DENGAN ANALISIS METODE ANALYTIC HIERARCHY PROCESS - Maulidya Khairani; Fibri Rakhmawati; Hendra Cipta (Jurnal Informatika Teknologi dan Sains, 2022)
The emergence of the Bus Trans Metro Deli Medan as a means of public transportation based on BRT (Bus Rapid Transit) has caused City Transportation in the city of Medan to feel competitive and the income earned has decreased due to passengers switching to its use. The purpose of this study is to apply the Analytic Hierarchy Processmethod to the factors that influence the people of Medan in using Bus Trans Metro Deli Medan and to find out the most priority factors. From the research results obtained by applying the Analytic Hierarchy Processthat 80% people of Medan prefer to use Bus Trans Metro Deli Medan with a fare factor of 24%, travel time is 9%, Convenience is 19%, Technology Development is 12%, Travel Accsess is 10%, Service is 15% and Life Style is 11%. So, the cost rate factors is more priority than other factors.